The influence of phytoplankton pigments composition and dominant cell size on fluorescence-derived photophysiological parameters and implications for primary production rates - Giannini, Maria Fernanda Colo (2016)
Phytoplankton chlorophyll-a fluorescence, measured in situ, can be applied as a tool to estimate primary production in the ocean over a large range of temporal and spatial scales. This non-invasive technique allows for fast assessments of photo-physiological parameters in contrast to the traditional methodologies (14C uptake and O2 evolution). The main photo-physiological parameters derived by the available instruments are yields, and as such, require careful interpretation. The comprehension of the main sources of variability of the photochemical and the light absorption efficiencies in marine phytoplankton has increased in the past years, largely by studies using monospecific cultures. In natural communities, however, the development of primary production models based on chlorophyll-a fluorescence remain limited as they are simultaneously subjected to a wide range of environmental and biological factors. This study will test the hypothesis that photo-physiological models for primary production estimates can be improved when key phytoplankton features, such as the pigments composition and dominant cell size, are taking into account. The approach was to contrast the photo-physiological parameters derived from measurements in distinct oceanographic regions, as well as those derived in a specific environment with presented different nutrient concentration according to the time of sampling. In addition, we showed for monospecific cultures, how the photo-physiological parameters are quantitatively related to the production of carbon under the interactive effects of taxonomic composition and cell size. The proportions of photosynthetic and photoprotective pigments present in the community were related to the bulk photochemical efficiency and the cross-section of light absorption, but varied among oceanographic regions and the depth of the water column. A parameterization of fluorescence-derived primary production rates, using four dominant size classes, was derived for natural phytoplankton communities under different nutrients conditions in a coastal environment, showing that the parameters differed among size classes above a threshold of nutrient concentration. The direct conversion rates between fluorescence-derived primary production and carbon assimilation rates, computed for two distinct phytoplankton cell sizes grown in controlled laboratorial conditions, showed that cell size strongly influences the efficiency of light absorption and photochemistry, however species-specific responses in photosynthetic energy allocation dominated the differences observed in how absorbed light is utilized to carbon assimilation, i.e., in the electron requirements for carbon assimilation. The results highlighted the importance of the tight coupling of nutrients availability and phytoplankton communities, as well as for measurements of chlorophyll-a fluorescence in the ocean and primary production models. This work presents a novel contribution to the increasing efforts to apply fluorescence-based techniques to understand and parameterize primary production estimates in marine systems, especially at highly dynamic environments.